SKRINING BAKTERI METANOTROF, PELARUT POSFAT DAN NITROBACTER PADA LAHAN PERTANIAN KOTA SORONG - S Sukmawati; P Ponisri; Febrianti Rosalina; Anif Farida; Budi Satria; Ayu Diah Syafaati; N Nuryanto (Fapetrik-UMPAR, 2022)
The effects of greenhouse gases on daily life can cause damage to the balance of ecosystems and threaten the survival of living things. One of them is crop failure; food commodities and export products are reduced, causing food shortages and lowering the economic level of the community. The initial objectives of this study were to find or filter methanotrophic, phosphate-solubilizing, and Nitrobacter bacteria on Sorong's agricultural land. The second aim was to determine methanotrophic bacteria's potential, which can also nitrate and solubilize phosphate. The findings of the screening for methanotrophic bacteria, phosphate-solubilizing bacteria, and Nitrobacter bacteria are described in this descriptive study. In addition, isolates of methanotrophic bacteria were confirmed for their ability to decompose phosphate and fix nitrogen. The results of this study were that of the ten samples observed, five samples were detected by methanotrophic bacteria, namely MFa, MFb, MFc, MFd, and MFe samples. Furthermore, phosphate-solubilizing bacteria and Nitrobacter bacteria were found in ten isolated samples. The second conclusion, from five isolates of methanotrophic bacteria, has the potential to decompose or utilize phosphate as an energy source. Meanwhile, of the five isolates, only three isolates could utilize nitrogen as an energy source, namely isolates with MFa code, MFd isolates, and MFe isolates.